Cultivation of Spirulina platensis using anaerobically swine wastewater treatment effluent - Siraporn Cheunbarn (2018)
In this study, Spirulina platensis was cultivated by using effluent from anaerobically treated swine wastewater at concentration of 0, 10, 20, 40, 60, 80 and 100% dilution. Results showed that the most suitable concentration for maximum growth of S. platensis was 10% dilution with NaHCO3 and NaNO3 at 8.0 g L-1 and 1.5 g L-1, respectively. From a batch culture with 10% dilute concentration and added nutrients, highest wastewater treatment efficiency occurred after 12 days retention time when maximum removal efficiency was measured at 23, 45, 49, 92 and 67% for COD, BOD, NO3-, NH4+ and PO43- respectively. Maximum growth of S. platensis was measured by 17.8×104 cells mL-1 and value of OD560 at 1.09 with 55.88 % protein content by dry weight. This suggested that S. platensis could be applied for use as a food nutrient in the farm that could decrease farm cost. © 2010 Friends Science Publishers.